(untitled) (Italian Review of Legal History, 2022)
Following some cues offered by excerpts from Goethe’s Elective Affinities, the essay aims at retracing the path followed by the German Historical School of Law in the 19th century, arguing about the technical and cultural issues that drove its progresses. The School’s internal debates, originated by its program for a scientifical attitude towards law, have to deal with the ways of relating to the past and valuing its products, and the jurists’ role within society. The described intinerary detects an unceasing pursuit of adequate dialogue between ‘being’ and ‘becoming’, past and present (and future), ‘system’ and ‘history’.